THE IMPLEMENTATION OF ORGANIZATIONAL BEHAVIOR AND JOB SATISFACTION FOR THE LEGAL AND HUMAN RESOURCES EMPLOYEES AT GREEN SCHOOL, BALI - Widanti, Ni Putu Tirka (DIA: Jurnal Administrasi Publik, 2022)
This study used a mixed-method comprising of a survey, interview, storing opinions, and sharing experiences with 63 participants. An interpretation was used in collecting the result of answer percentage from the respondents in the questionnaires, interviews, and sharing experiences in group discussion. The research finding showed that there is an issue faced by the employees and there were also responses from the participants concerning the organizational behavior and job satisfaction in the organization obeyed by the employees during their working time.